2010
DOI: 10.1007/s11689-010-9049-0
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus specific iron deficiency alters competition and cooperation between developing memory systems

Abstract: Iron deficiency (ID) is the most common gestational micronutrient deficiency in the world, targets the fetal hippocampus and striatum and results in long-term behavioral abnormalities. These structures primarily mediate spatial and procedural memory, respectively, in the rodent but have interconnections that result in competition or cooperation during cognitive tasks. We determined whether ID-induced impairment of one alters the function of the other by genetically inducing a 40% reduction of hippocampus iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 70 publications
(128 reference statements)
2
56
0
1
Order By: Relevance
“…Disruption of this process by nutritional deficiency during foetal, childhood, or adolescent development has been linked to behavioural and neuronal deficits707172. In the developing brain, iron is closely related to neuro-inflammation, potentially caused by stress and nutrition73.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this process by nutritional deficiency during foetal, childhood, or adolescent development has been linked to behavioural and neuronal deficits707172. In the developing brain, iron is closely related to neuro-inflammation, potentially caused by stress and nutrition73.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the hippocampus is essential for the development of many behaviors (including learning and memory) and that low iron can negatively affect behavioral development (49). Iron deficiency can disrupt the dopamine pathway to alter certain forms of learning (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Of the significant genes in this pathway, Slc11a2 deficiency has been associated with hippocampal iron levels and related cognitive and neurodevelopmental traits in rodents (Carlson et al, 2010;Pisansky et al, 2013). VAMP7 is suggested to play a role in neural transmission (Bal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%